Wood biomass of one gallery forest - Imaña-Encinas, José; de Paula, José Elias; Kleinn, Christoph (Pesquisa Agropecuaria Brasileira, 1995)
On a study in a gallery forest at the small stream Dos Macacos situated at Santo Antônio do Descoberto, GO, Brazil, an area of one hectare was analysed. On 1.741 trees the wood volume with bark and the dry wood biomass of stems and branches was determined for trees with a DBH greater than 5 cm. 117 species were identified. The total volume was 181,996 m3/ha corresponding to 132 tons of dry wood. The results could form a base for management plans, utilizing these resources on a sustainable yield basis.